TIMING AND DURATION OF KIMBERLITIC MAGMATISM IN THE ZIMNII BEREG DIAMONDIFEROUS PROVINCE: EVIDENCE FROM RB-SR AGE DATA ON KIMBERLITE SILLS ALONG THE MELA RIVER - Pervov V.A.; Larchenko V.A.; Minchenko G.V.; Stepanov V.P.; Bogomolov E.S.; Levskii L.K.; Sergeev S.A. (My University, 2006)
Determination of the age boundaries of magmatic activity and elucidation of the sequence of magmatic eruptions in certain magmatic provinces allow correlation of magmatic events over wide areas. This is of great importance for understanding the reasons and manner of evolution of deep magmatic processes. Kimberlites and lamproites were emplaced in the East European Craton (in particular, in the Baltic Shield and adjacent areas) in several stages. The Devonian stage was marked by the wide occurrence of alkaliultramafic rocks (including kimberlites) in the Baltic Shield (Kola Peninsula and Karelia), Arkhangelsk district, Middle Timan, and Ukrainian Shield (eastern Azov region).
Keywords: Baltic shield; Палеозой::Девонская